(untitled) (Journal of Contemporary Philology, 2024)
The position that Barthes holds when reading Proust can be easily characterized today, thanks to the publication of Barthes’ main texts about Proust in Marcel Proust, Mélanges (2020). Barthes’ reading of Proust highlights the play of a duality between ‘sense’ and ‘field of sense’ in À la recherche du temps perdu (In Search of Lost Time). It also examines the specific temporality of the narrative, which enforces an equality of past, present, and future, as well as the remarkable reflexivity and conclusion of the novel that makes Proust’s past the future of the narrator. Barthes’ comments on À la recherche du temps perdu illuminate and revise the main concepts of his literary theory, and find in the interplay of the sense/field of sense duality a means to redefine literature on one hand, and on the other, to surpass the critical impasses addressed in Le Degré zéro de l’écriture (Writing Degree Zero).